1D Colloidal Hetero‐Nanomaterials with Programmed Semiconductor Morphology and Metal Location for Enhancing Solar Energy Conversion. Issue 13 (30th January 2017) - Zhuang, Tao‐Tao; Liu, Yan; Li, Yi; Sun, Meng; Sun, Zi‐Jun; Du, Ping‐Wu; Jiang, Jun; Yu, Shu‐Hong
Abstract : A new kind of multitetrahedron sheath ternary ZnS‐(CdS/Au) hetero‐nanorod is prepared, in which one 1D ultrathin ZnS nanorod is integrated with segmented tetrahedron sheaths made of CdS, and more importantly, Au nanoparticles can be decorated in a targeted manner onto the vertexes and edges of CdS tetrahedron sheaths solely, for achieving performance improvement in photoelectric and photochemical conversion applications.